Computing interior transmission eigenvalues for homogeneous and anisotropic media. (20th August 2018) - Kleefeld, Andreas; Pieronek, Lukas
Abstract: The method of fundamental solutions is investigated in a stabilized version for the computation of interior transmission eigenvalues in two dimensions for homogeneous and anisotropic media without voids. This approach has already proven to be very competitive in practice for the isotropic framework among regular scattering shapes and keeps predominating through its simplicity as being mesh- and integration free. We give a new approximation analysis, present various numerical results and show that the eigenvalue spectrum for isotropic scatterers is generally different from the corresponding anisotropic borderline cases.